The Effect of Interactive Video on Social Studies Learning Motivation for Fifth Grade at SDN Kaliwungu 2 Jombang - Nur Laila, Umi; Fitra Raharja, Hawwin (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
Thisâ€œstudy aims to determine the effect of interactive video media on students learning motivation in social studies of fifth grade at SDN Kaliwungu 2 Jombangâ€which refers to the thematic book class V â€œtheme 7 events in life, sub-theme 2 national events surrounding the proclamation of learning independence 1â€. The problems in education were the learning implementation is less attractive. For that,â€œthe teachers are required to be creative in improving the quality of learning such as using media inâ€learning. One of the interesting learning media is interactive video media. Research using interactive video media in social studies learning was carried out in the even semester of the 2020/2021 school year. The research used experimental research with pre-experimental method and one group pre-test post-test design. The population in this study were all fifth grade students at SDN Kaliwungu 2 Jombang which consisted of 20 students, 11 female students and 9 male students. The results of the study can be seen from the t test (paired t test) obtained t_count (4.0376) > t_table (2.0930). From these results it can be concluded that there is